1994
DOI: 10.1212/wnl.44.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The British Isles survey of multiple sclerosis in twins

Abstract: During a 27-month recruitment period, we identified 146 individuals with multiple sclerosis (MS) who have a twin. A single clinician interviewed and examined 105 pairs of twins, and we confirmed zygosity using minisatellite probes. Including two suspected cases, 11 of 44 (25%) monozygotic twin pairs were concordant compared with two of 61 (3%) dizygotic twin pairs--two of 33 (6%) like-sexed and zero of 28 (0%) opposite-sexed. MRI was performed in 64 of 105 co-twins, and showed abnormalities consistent with dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(158 citation statements)
references
References 0 publications
6
145
0
7
Order By: Relevance
“…The percentage of concordance for monozygotic twins is approximately 25-30% whereas the concordance percentage for dizygotic twins is 3-5% (Ebers et al, 1986(Ebers et al, , 1995(Ebers et al, , 2004Mumford et al, 1994;Willer et al, 2003;Hansen et al, 2005;Islam et al, 2006;Ristori et al, 2006). This concordance rate for fraternal twins is greater than that of other first-degree relatives of MS patients but is still far less than that of identical twins (Willer et al, 2003).…”
Section: Twin Studiesmentioning
confidence: 99%
“…The percentage of concordance for monozygotic twins is approximately 25-30% whereas the concordance percentage for dizygotic twins is 3-5% (Ebers et al, 1986(Ebers et al, , 1995(Ebers et al, , 2004Mumford et al, 1994;Willer et al, 2003;Hansen et al, 2005;Islam et al, 2006;Ristori et al, 2006). This concordance rate for fraternal twins is greater than that of other first-degree relatives of MS patients but is still far less than that of identical twins (Willer et al, 2003).…”
Section: Twin Studiesmentioning
confidence: 99%
“…Although the exact cause of multiple sclerosis is unknown, epidemiological studies indicate a multifactorial aetiology 1 with the involvement of genetic factors suggested by studies in twins, 2,3 half-siblings, 4 adoptees 5 and conjugal pairs. 6,7 The role of major histocompatibility complex (MHC) class II alleles is well established, 8 but no other candidate genes have consistently been linked or associated with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed a higher concordance rate between identical (monozygotic) compared with nonidentical (dizygotic) pairs (approximately 25–30% in monozygotic versus 5% in dizygotic twins) 50, 51. In contrast, other studies showed equivalent concordance rates 52, 53…”
Section: Genetic and Environmental Risk Factorsmentioning
confidence: 99%